Caesarean scar ectopic pregnancy: a case report - Kailash, Nishi; Trivikrama, Heera Shenoy; ., Shivakumar; Kuniyil, Sajitha Ambichi; Sabarmathi, Chandni; Ramakrishnan, Janaky; Kunheen, Safa (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Caesarean scar ectopic pregnancy (CSEP) is where the conceptus is implanted deep in the myometrium and at the exact scar site of the previous caesarean section. Symptoms include amenorrhea, pelvic pain and vaginal bleeding in the first trimester. The investigation of choice is transvaginal ultrasound. Individualized treatment options are based on gestational age, presence of embryonal cardiac activity, severity of symptoms, serum hCG levels and ultrasonography findings for CSEP. The combined use of laparoscopy and ultrasound guidance for the evacuation is helpful in deeply impacted CSEP. Because early diagnosis and treatment is important for the best outcome, every pregnant woman with a history of cesarean should be screened early in the first trimester of pregnancy.